Precise mapping and dynamics of tRNA-derived fragments (tRFs) in the development of Triops cancriformis (tadpole shrimp) - Hirose, Yuka (BMC Genet, 2015)
BACKGROUND: In a deep sequencing analysis of small RNAs prepared from a living fossil, the tadpole shrimp Triops cancriformis, a 32-nt small RNA was specifically detected in the adult stage. A nucleotide sequence comparison between the 32-nt small RNA and predicted tRNA sequences in the draft nuclear genomic DNA showed that the small RNA was derived from tRNA(Gly)(GCC). To determine the overall features of the tRNA-derived fragments (tRFs) of T. cancriformis, the small RNA sequences in each of the six developmental stages (egg, 1st − 4th instar larvae, and adult) were compared with the mitochondrial and nuclear tRNA sequences. RESULTS: We found that the tRFs were derived from mitochondrial and nuclear tRNAs corresponding to 16 and 39 anticodons, respectively. The total read number of nuclear tRFs was approximately 400 times larger than the number of mitochondrial tRFs. Interestingly, the main regions in each parental tRNA from which these tRFs were derived differed, depending on the parental anticodon. Mitochondrial tRF(Ser)(GCU)s were abundantly produced from the 5’ half regions of the parental tRNA, whereas mitochondrial tRF(Val)(UAC)s were mainly produced from the 3’ end regions. Highly abundant nuclear tRFs, tRF(Gly)(GCC)s, tRF(Gly)(CCC)s, tRF(Glu)(CUC)s, and tRF(Lys)(CUU)s were derived from the 5’ half regions of the parental tRNAs. Further analysis of the tRF read counts in the individual developmental stages suggested that the expression of mitochondrial and nuclear tRFs differed during the six stages. Based on these data, we precisely summarized the positions of the tRFs in their parental tRNAs and their expression changes during development. CONCLUSIONS: Our results reveal the entire dynamics of the tRFs from both the nuclear and mitochondrial genomes of T. cancriformis and indicate that the majority of tRFs in the cell are derived from nuclear tRNAs. This study provides the first examples of developmentally expressed mitochondrial tRFs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12863-015-0245-5) contains supplementary material, which is available to authorized users.